2020
DOI: 10.1142/s1793351x20400048
|View full text |Cite
|
Sign up to set email alerts
|

Click-Through Rate Prediction of Online Banners Featuring Multimodal Analysis

Abstract: As the online advertisement industry continues to grow, it is predicted that online advertisement will account for about 45% of global advertisement spending by 2020.a Thus, predicting the click-through rates (CTRs) of advertisements is increasingly crucial for the advertisement industry. Many studies have already addressed the CTR prediction. However, most studies tried to solve the problem using only metadata such as user id, URL of the landing page, business category, device type, etc., and did not include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…For the analysis of online advertising, we are conducting joint research with SEPTENI CO., LTD., one of the major agencies of online advertisement in Japan. By our own deep learning architecture, we have succeeded in predicting CTR values in advance with a correlation coefficient of 0.82 [27], [28] for still image advertisements and 0.70 [29] for video advertisements. By predicting advertising effectiveness with high accuracy in advance, it is possible to arrange advertisements efficiently and effectively without conducting AB tests, etc.…”
Section: Design Generation Support For Advertisingmentioning
confidence: 99%
“…For the analysis of online advertising, we are conducting joint research with SEPTENI CO., LTD., one of the major agencies of online advertisement in Japan. By our own deep learning architecture, we have succeeded in predicting CTR values in advance with a correlation coefficient of 0.82 [27], [28] for still image advertisements and 0.70 [29] for video advertisements. By predicting advertising effectiveness with high accuracy in advance, it is possible to arrange advertisements efficiently and effectively without conducting AB tests, etc.…”
Section: Design Generation Support For Advertisingmentioning
confidence: 99%
“…In online advertising, there are two main prediction tasks: Click Through Rate (CTR), 11,8 predicting if an ad link is clicked when a user views a webpage or app; and CVR, 7 estimating if there will be a sale when an ad is viewed. Under the analyzed MPM domain, the CTR probability is always 100% since users need to click an ad before accessing the publisher content (e.g., news portal).…”
Section: Related Workmentioning
confidence: 99%
“…Although many studies have worked on the effects of image advertising [1]- [3], there are seldom research on video advertising. In particular, to our knowledge, research on predicting the CTR for online video ads has not been conducted extensively.…”
Section: Ctr = Number Of Clicks Number Of Impressionsmentioning
confidence: 99%
“…These methods dealt primarily with metadata. Chen et al [10] showed the effectiveness of using features extracted from images by convolutional neural networks (CNNs) for prediction; Iwazaki [1] proposed a method to use features from text extracted by CNNs in addition to images and metadata; Xia et al [2], [3] showed that extracting features from embedded text improved prediction accuracy. In addition, they visualized the contribution of images, metadata, Fig.…”
Section: A Ctr Predictionmentioning
confidence: 99%